Taxonomic notes on Dendrobium sect. Pedilonum (Orchidaceae): a new species, D. nakhonsiense, from Thailand and the D. cumulatum s.l. complex revisited - Rujichaipimon, Wirata; Pedersen, Henrik Æ.; Suddee, Somran; Traiperm, Paweena (Phytotaxa, 2026)
This study presents a classical taxonomic approach to parts of Dendrobium sect. Pedilonum, focusing on a newly discovered species from Thailand and the D. cumulatum s.l. species complex. The new species, D. nakhonsiense seems endemic to Nakhon Si Thammarat Province in Peninsular Thailand where it is only known from one location. It is morphologically close to D. cowenii but is distinguished by its slightly larger flowers with a relatively longer, obtuse to rounded mentum and by its differently shaped dorsal sepal and labellum lamina. The D. cumulatum s.l. complex includes four taxa, viz. D. cumulatum, D. rhodocentrum, D. eoum, and D. calicopis. Based on extensive herbarium studies and morphological comparisons, we propose the recognition of two distinct species: D. cumulatum (syn.: D. rhodocentrum, D. calicopis) and D. eoum. Our findings contribute to the understanding of species diversity and distribution within Dendrobium sect. Pedilonum.